The New Institutional Economics: Taking Stock, Looking Ahead - Williamson, Oliver E (Journal of Economic Literature, 2000)
This paper examines the progressive development of the new institutional economics over the past quarter century. It begins by distinguishing four levels of social analysis, with special emphasis on the institutional environment and the institutions of governance. It then turns to some of the good ideas out of which the NIE works: the description of human actors, feasibility, firms as governance structures, and operationalization. Applications, including privatization, are briefly discussed. Its empirical successes, public policy applications, and other accomplishments notwithstanding, there is a vast amount of unfinished business.